The Transhistorical Tension between Bureaucratic Autonomy and Political Control. (August 2019) - Andersen, David; Møller, Jørgen
Political decision-makers operate under a constant tension between bureaucratic autonomy on one hand and political control on the other. Extant scholarship rarely analyzes this tension beyond the context of modern states. However, three recent books show that it has a transhistorical relevance. Francis Fukuyama's two volumes on The Origins of Political Order and Political Order and Political Decay analyze the various ways the tension has been addressed in the period before and after the French Revolution. In Democracy's Slaves, Paulin Ismard documents that the tension was relevant even in the context of the direct democracy of Athens in the Classical period. Taking these three books as the point of departure, we show how politicians have attempted to balance autonomy and control in patrimonial, meritocratic, politicized, and neo-patrimonial types of administration. Fukuyama F (2012) The Origins of Political Order, vol. 1. London: Profile Books. Fukuyama F (2014) Political Order and Political Decay, vol. 2. London: Profile Books. Ismard P (2017) Democracy's Slaves: A Political History of Ancient Greece . Cambridge, MA: Harvard University Press.